Students' Reading Comprehension in Relation to Learning Style: A Case Study at SMA Insan Cendekia - Sitti Zakiyah Amrullah; Sukardi Weda; La Sunra (ARRUS Journal of Social Sciences and Humanities, 2024)
This research aims to find out whether or not the use of the six thinking hats strategy improves the students’ writing ability. The research was conducted to determine students' reading comprehension levels based on each learning style. This research is a qualitative descriptive method. The subject of this research were students of in second year student at SMA Insan Cendekia. The instruments used in this research were reading comprehension test, The VARK 8.0 questionnaire, and interview. The results of the reading comprehension test, the researcher used two level in reading comprehension. They are literal comprehension level and inferential comprehension level. The results showed that students with Visual learning style has a problem on inferential level, auditory learning style with inferential and literal level, read/write face a problem with inferential and literal, and kinesthetic learning style experiences problem both with literal and inferential level.